2010
DOI: 10.1073/pnas.1008296107
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental limit of nanophotonic light trapping in solar cells

Abstract: Establishing the fundamental limit of nanophotonic light-trapping schemes is of paramount importance and is becoming increasingly urgent for current solar cell research. The standard theory of light trapping demonstrated that absorption enhancement in a medium cannot exceed a factor of 4n 2 ∕ sin 2 θ, where n is the refractive index of the active layer, and θ is the angle of the emission cone in the medium surrounding the cell. This theory, however, is not applicable in the nanophotonic regime. Here we develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
458
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(471 citation statements)
references
References 41 publications
13
458
0
Order By: Relevance
“…Despite the early work suggesting that the absorption enhancement in thin slabs is less than 4n 2 , recent work has shown that the enhancement may in fact exceed this limit through the use of photonic crystals, 5 plasmonic waveguides, 6 and high index claddings, 7,8 which all elevate the local density of optical states to achieve enhancment. 9 Here we revisit the case of a thin waveguide and determine that the 4n 2 limit can be exceeded for a number of structures that support large propagation constants and/or slow modal group velocities.…”
Section: Limit In Thin Waveguidesmentioning
confidence: 99%
“…Despite the early work suggesting that the absorption enhancement in thin slabs is less than 4n 2 , recent work has shown that the enhancement may in fact exceed this limit through the use of photonic crystals, 5 plasmonic waveguides, 6 and high index claddings, 7,8 which all elevate the local density of optical states to achieve enhancment. 9 Here we revisit the case of a thin waveguide and determine that the 4n 2 limit can be exceeded for a number of structures that support large propagation constants and/or slow modal group velocities.…”
Section: Limit In Thin Waveguidesmentioning
confidence: 99%
“…11 For nonsilicon absorbers with low refractive index it was proposed that embedding between high index cladding layers can enhance the absorption beyond the 4n 2 limit via coupling to evanescent fields. 12,13 In this contribution, we discuss the absorption enhancement in realistic thin film solar cells based on amorphous silicon (a-Si). Our considerations are based on the modal properties of an equivalent multilayer stack, using realistic values for the thicknesses and the refractive index dispersion of all components.…”
Section: Introductionmentioning
confidence: 99%
“…This can either lead to enhanced absorption, or can reduce the amount of required material and hence reduce fabrication costs. Nanophotonics offers interesting possibilities for improving solar cell absorption [14][15][16]. Standard optics is limited by an upper thermodynamical limit [17], which can however be surpassed by nanophotonic strategies in particular when the absorbing films are extremely thin [18].…”
Section: -Introductionmentioning
confidence: 99%
“…Through different photonic architectures it is possible to augment the optical absorption by, for instance, trapping light within ultra-thin films [14], or even manipulate the photon density of state [15] or slowing down light in absorbing thin films. This can be achieved by periodic photonic structures [14,15] or disordered ones [19][20][21], as it has been recently proposed in a two-dimensional system [22] in which disorder modes are on the verge of light (Anderson) localization [23][24][25].…”
Section: -Introductionmentioning
confidence: 99%